Makularno krvarenje izazvano 3,4-methilenedioksimetamfetaminom (MDMA): prikaz slučaja - Đogatović, Nebojša; Potkonjak, Ernesta; Račić, Vladimir; Milićević, Miloš; Abdulaj, Dajana; Kozomara, Bojan (Scripta Medica, 2021)
A case of 28-year-old female patient with retinal haemorrhage after taking 3,4-methylenedioxymethamphetamine (ecstasy, MDMA) and having a sexual intercourse is described. Ecstasy is a drug that is often consumed by young people. It leaves various consequences on the human body. Retinal haemorrhage in the eye caused by ecstasy has been described before. Like in this case, the experience in spontaneous resolving of the MDMA-induced retinal haemorrhage is favourable.
Keywords: Zabranjene supstancije; 3,4-methilenedioksimetamfetamin; Krvarenje u retini